Optogenetic silencing of a corticotropin-releasing factor pathway from the central amygdala to the bed nucleus of the stria terminalis disrupts sustained fear - Asok, Arun (Mol Psychiatry, 2017)
The lateral central nucleus of the amygdala (CeA(L)) and the dorsolateral bed nucleus of the stria terminalis (BNST(DL)) coordinate the expression of shorter and longer-lasting fears, respectively. Less is known about how these structures communicate with each other during fear acquisition. One pathway, from the CeA(L) to the BNST(DL,) is thought to communicate via corticotropin-releasing factor (CRF), but studies have yet to examine its function in fear learning and memory. Thus, we developed an adeno associated viral-based strategy to selectively target CRF neurons with the optogenetic silencer archaerhodopsin tp009 (CRF-ArchT) to examine the role of CeA(L) CRF neurons and projections to the BNST(DL) during the acquisition of contextual fear. Expression of our CRF-ArchT vector injected into the amygdala was restricted to CeA(L) CRF neurons. Furthermore, CRF axonal projections from the CeA(L) clustered around BNST(DL) CRF cells. Optogenetic silencing of CeA(L) CRF neurons during contextual fear acquisition disrupted retention test freezing 24 hours later, but only at later time-points (> 6 minutes) during testing. Silencing CeA(L) CRF projections in the BNST(DL) during contextual fear acquisition produced a similar effect. Baseline contextual freezing, the rate of fear acquisition, freezing in an alternate context after conditioning and responsivity to foot-shock were unaffected by optogenetic silencing. Our results highlight how CeA(L) CRF neurons and projections to the BNST(DL) consolidate longer-lasting components of a fear memory. Our findings have important implications for understanding how discrete amygdalar CRF pathways modulate longer-lasting fear in anxiety- and trauma-related disorders.